(untitled) (Journal of the College of Basic Education, 2025)
This study discusses the use of fuzzy control charts as an effective tool to improve control processes in complex systems, particularly in industrial and environmental applications. Fuzzy control systems are characterized by their ability to handle vague and imprecise information, making them an ideal choice for managing pH levels and addressing water pollution. The study utilized the Average Chart with Fuzzy Range (), the Fuzzy Range Chart (), and the Fuzzy Cumulative Sum Chart (FCUSUM) to detect shifts in data represented by fuzzy triangular numbers for controlling water pollution and monitoring varying quality characteristics. These charts were applied to real data collected over 60 days from water sources. The results revealed a variation in the number of samples exceeding control limits among the charts used in the study. By employing comparison criteria such as the Capability Index (), Capability Performance (), and Average Run Length (ARL), differences in chart performance were analyzed.